2018
DOI: 10.1089/mdr.2017.0316
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella Species' Persistence and Their High Level of Antimicrobial Resistance in Flooded Man-Made Rivers in China

Abstract: Man-made rivers, owing to proximity to human habitats, facilitate transmission of salmonellosis to humans. To determine the contamination situation by Salmonella in flooded man-made rivers and thereafter the exposure risk to public health, we investigated the prevalence of Salmonella species and their antimicrobial resistance in such rivers, as well as the relationship between the incidence of local infectious diarrhea cases and the number of Salmonella isolates from patients. After a heavy flood, 95 isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…We also found that ARG profiles of S. enterica isolates cultured from both flooded and unflooded samples were similar, suggesting that the 2018 flooding did not spread ARG detected in S. enterica isolates. This finding is consistent with the study conducted by Song et al (2018), which found that antibiotic resistance was prevalent in Salmonella spp. in flooded human-made rivers.…”
Section: Accepted Articlesupporting
confidence: 93%
See 2 more Smart Citations
“…We also found that ARG profiles of S. enterica isolates cultured from both flooded and unflooded samples were similar, suggesting that the 2018 flooding did not spread ARG detected in S. enterica isolates. This finding is consistent with the study conducted by Song et al (2018), which found that antibiotic resistance was prevalent in Salmonella spp. in flooded human-made rivers.…”
Section: Accepted Articlesupporting
confidence: 93%
“…In natural disasters such as flood events, livestock may experience a higher level of stress, and their immune system will be weakened as a result (Filipe et al, 2020), increasing the susceptibility of agricultural animals to Salmonella infections (Stevens et al, 2009). Previous studies show that Salmonella were prevalent and also resistant to antibiotics after flood events in rural settings (Bergholz et al, 2016;Divakaran et al, 2019;Song et al, 2018). For these earlier studies, Salmonella was detected and quantified by culturing samples on solid, selective microbiological culture media.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has become one of the major pathogens of nosocomial and foodborne infection and food poisoning. And it is more common in food poisoning and sepsis of infants and young children 11,12 . Salmonella typhimurium L forms often occur in patients after β-lactam antibiotic treatment, resulting in chronic infection.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Yes (2) Unable to test (1a) These associations were strongest for bacterial and all-cause diarrhea (1b) The strongest positive associations were 4-7 days after flood events (2) Studies often did not report the length of flood events in the literature 26 articles (Abu and Codjoe 2018, Cash et al 2014, Cesa et al 2016, Colston et al 2020, Deilami et al 2017, Fredrick et al 2015Gao et al 2016, Gertler et al 2015, Gong et al 2019, Jones et al 2016, Koley et al 2014, Liu X et al 2016, Liu Z et al 2018, Martinez et al 2016, Natuzzi et al 2016, Rosinger 2018, Saulnier et al 2018, Song Q et al 2018, Thompson et al 2015…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%